An examination of the factors involving students' acceptance of online educational games / Norlaila Ibrahim ... [et al.] - Ibrahim, Norlaila; Abdol Ghapar, Marha; Shamsudin, Azlina; Nik Hassan, Nik Fakrulhazri; Johar, Norchahaya (Universiti Teknologi MARA, Perlis, 2021)
Educators all over the world are scrambling to develop new and more advanced methods of teaching through the use of technology, with the common goal of engaging students in classrooms. Furthermore, the new generation, which grew up with the internet, video games, and online gaming, prefers a technology-infused approach to teaching and learning. They are no longer interested in the traditional method of classroom lectures. Educational games (EG) have also become a hot topic in the academic community. The goal of this paper is to look into the factors that influence students' acceptance of online education. Based on the literature review's discussions and arguments, it is possible to conclude that all factors influence students' acceptance of online EG.